The Effect of Physical Exercise on Depression in College Students: The Chain Mediating Role of Self-Concept and Social Support - Zhang, Junliang; Zheng, Shuang; Hu, Zhongzheng (Frontiers in Psychology, 2022)
Objective: To explore the effect of physical exercise on depression of college students and to understand the mechanism of social support and self-concept. Methods :The survey was conducted among 1200 college students in Jiangxi of China . Serial mediation models were used to examine whether self-concept and social support mediated in the physical exercise-depression. Results: Physical exercise significantly negatively predicted college depression.Moreover, Self-concept and social support play a chain mediating role between physical exercise and college students' depression. Conclusion:This study reveals the predictive effect of physical exercise on college students' depression and its mechanism, and the results have certain enlightenment significance for maintaining and promoting college students' physical and mental health.